1999
DOI: 10.1115/1.2841219
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Flow Analysis in a Subsonic Vaned Radial Diffuser With Leading Edge Redesign

Abstract: The flow field in a subsonic vaned radial diffuser of a single-stage centrifugal compressor is numerically investigated using a three-dimensional Navier–Stokes solver (TASCflow) and a two-dimensional analysis and inverse-design software package (MISES). The vane geometry is modified in the leading edge area (two-dimensional blade shaping) using MISES, without changing the diffuser throughflow characteristics. An analysis of the two-dimensional and three-dimensional effects of two redesigns on the flow in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…In Casartelli et al (1997) the redesign procedure was presented. The CFD results were validated by comparing the pressure rise (Dp) vs. flow coefficient (9) characteristic for the standard and a redesigned geometry, showing that the measured tendencies were properly captured numerically.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In Casartelli et al (1997) the redesign procedure was presented. The CFD results were validated by comparing the pressure rise (Dp) vs. flow coefficient (9) characteristic for the standard and a redesigned geometry, showing that the measured tendencies were properly captured numerically.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…In Casartelli et al (1997) a strategy has been presented for the redesign of the leading edge domain of vaned diffusers. It was based on the 2D analysis/ inverse design software MISES by Drela a al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yoshinaga et al [8] experimentally studied the effect of diffuser inlet on the stage efficiency of a model compressor rig, and the results showed that the leading edge shape of vanes had considerable influence on the performance. Casartelli et al [9] modified the vane leading edge geometry in a subsonic radial diffuser. Their numerical results showed that the stage performance could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is specially designed for the visualisation of large-scale flow phenomena like rotating stall (Gyarmathy (1996), File et al (1997)). Furthermore CFD calculations are performed with the TascFlow code (Casartelli et al (1997(Casartelli et al ( , 1998). Of special interest for experiments and CFD calculations is the flow field in the diffuser, because this part is mainly responsible for limiting the stable operating range.…”
Section: Introductionmentioning
confidence: 99%